Genetic framework of type 2 diabetes mellitus - Irina Arkad'evna Bondar' (Endocrinology Research Centre, 2013)
More than 100 genes associated with the risk of type 2 diabetes mellitus (T2DM) are now established. Most of them affect insulin secretion, adipogenesis and insulin resistance, but the exact molecular mechanisms determining their involvement in the pathogenesis of T2DM are not understood completely.